EFFECT OF LIME ON STABILIZATION OF MINING WASTE FROM SABAH, MALAYSIA (Malaysian Journal of Civil Engineering, 2018)
This paper deals with the effect of lime on stabilization of mining waste from Sabah, Malaysia. In this study, different percentages of lime as well as fine material were added as additive with the mining waste. The engineering properties were measured by compaction test, unconfined compressive strength tests and permeability tests. The mineral identification and microstructure were examined using X-ray diffraction (XRD) and Scanning Electron Microscopic (SEM). The compaction test indicated that the optimum moisture content varied with amount of lime content. The virgin mining waste showed low unconfined compressive strength value due to the very low cementing agent. The samples showed a rapid increase in shear strength when stabilized with lime content ranging from 2 to 8%. The rate of increase in strength is most rapid within two weeks of interaction. This is due to the pozzolanic reaction, which created more rigid - packed structure and small pore space at lime content as low as 2%. More addition of lime had increased the unconfined compressive strength due to the intensive pozzolanic reactions forming more cementitious mineral and created bridge-like structure. However the optimum percentage of lime required was 6% based on the unconfined compressive strength. Lime content in excess of the optimum (8% of lime) acted as filler or lubricant. Significant reduction in permeability to 1 x 10-7 m/s was observed at the end of the leaching test. This is due to the development of cementitious minerals and clogging of fine particle size in the pore spaces.